PERSEPSI SISWA TERHADAP PENERAPAN FLIPPED CLASSROOM PADA PEMBELAJARAN IPA SECARA DARING DI KELAS IX SMP NEGERI 2 TANJUNGPINANG - Ersa Mayola; Bony Irawan; azza Nurullah Putri (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2022)
Flipped classroom has become emerging trend during pandemic and require investigation to its application in a typical Indonesian school. This quantitative study aimed to shed light into student perceptions on the application of the flipped classroom in class IX at SMP Negeri 2 Tanjungpinang. The sampling technique used was random sampling. Student perceptions were measured from 134 respondents. Data were collected using likert scaled questionnaire followed by interview. In general, students have good perceptions about science learning conducted in flipped classroom learning model (71%). Specifically, respondents perceived the application of flipped as meaningful, as well as promoting core competence. This study concluded flipped classroom to be applicable in most learning scenario in Indonesian school.